The Role of Academic Flow in Enhancing Student Engagement Among High School Students - Sagita Pratiwi; Muhammad Muhajirin; Cucu Arumsari (Edupotensia Foundation, 2025)
Academic flow and student engagement are essential components of the learning process that influence students’ focus, intrinsic motivation, and academic success. According to Csikszentmihalyi’s (1990) flow theory, experiencing deep involvement in learning activities that are both challenging and aligned with one’s abilities can enhance concentration and persistence. Similarly, the engagement framework by Fredricks et al. (2004) emphasizes that behavioral, emotional, and cognitive engagement is shaped by positive and meaningful learning experiences. This study aims to describe the levels of academic flow and student engagement among 11th-grade students at SMK Negeri Manonjaya and to analyze the relationship between the two variables. Using a quantitative correlational approach with standardized measurement scales, the findings show that academic flow falls within the moderate category (78.48%), and student engagement is also in the moderate category (66.82%). Pearson correlation analysis reveals a strong and significant positive relationship between academic flow and student engagement (r = 0.684, p < 0.001), while regression analysis indicates that academic flow contributes 46.7% to student engagement. These results suggest that higher levels of flow—reflected in students’ focus, enjoyment, and interest in learning—are associated with higher academic engagement. A limitation of this study is that it did not incorporate any intervention; thus, it provides only a descriptive overview of students’ conditions without examining the effectiveness of specific actions to improve flow or engagement. Practical implications emphasize the role of classical guidance services, with materials such as enjoyable study strategies, learning responsibility, social ethics, coping with challenges, improving concentration, creativity development, wise decision-making, and learning motivation. These materials can strengthen students’ self-regulation, focus, resilience, positive interactions, and intrinsic motivation, thereby supporting the development of optimal flow conditions and academic engagement.